Three Years Experience in the Management of Uterine Rupture at Al-Battool Teaching Hospital Mosul-Iraq - Sarsam, Samar D. (AL-Kindy College Medical Journal, 2008)
Background: Ruptured uterus is a catastrophic event to bothmother and her fetus. Apart from maternal and fetal mortalityrates, the incidence of rupture of uterus is often taken as anindex of the standard of obstetric care.Objective: To determine the frequency, causes, managementoutcome of ruptured uterus at Al Batool maternity hospital.Method: The study was conducted in the department ofobstetrics and gynecology at Al Batool maternity hospitalMosul-Iraq over a period of three years from October 1st 2002to August 30th 2005. All the cases of uterine rupture presentedduring the study period were recorded and managed in thedepartment. Data was recorded on designed forms.Results: Thirty nine cases of ruptured uterus out of 44539deliveries were registered, the incidence was 0.087%. Ageranged from 15 to45 years. The majority of the patients weregrandmultipara (Para 5 and above), but 7 of the patients werenulliparous women (17.94%). 26 ruptures (66.66%) occurredin unscarred uterus and 13 ruptures (33.33%) occurred inscarred uterus, cephalopelvic disproportion and obstructedlabor were the cause of rupture in 11 cases (28.2%), inaddition to the mentioned causes 11 cases of the uterineruptures we registered in our study (28.2%) were mishandledby the traditional birth attendants, and in 14 cases (35.89%)there was injudicious use of oxytocin. We had three maternaldeaths (7.69%) out of 39 patients, and only 10 fetuses out of39(25.64%) were alive.Conclusion: Rupture uterus is still an important cause ofmaternal and perinatal mortality and morbidity in Iraq, it isnot always suspected, and hence increased vigilance is vital.Further studies may help in the development of preventivestrategies and ensure prompt management to reduce maternaland perinatal mortality and morbidity